Pengaruh Inokulasi Rhizobium-CMA Terhadap Pertumbuhan dan Hasil Dua Varietas Kedelai Pada Tanah Entisol - Utari, Lilik; Isnawan, Bambang Heri; Khusna, Farida (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A research to observe  the influence of Rhizobium and Vesicular Arbuscular Mycorrhyzae inoculation  on growth  and yield of Edamame and Wilis varieties of soybeans in Entisol  soil. The research  was conducted  in the green house  of Agriculture  Faculty,  Muhammadiyah   University  of Yogyakarta,  from June to September  2003. The field experiment  was arranged  in 4x2 factorial  Completely  Randomized  Design  (CRD) with three  replications.   The  first  factor  was  inoculation treatment which contains four  levels consisted  of:   (1) without  inoculation;   (2) Rhizobium inoculation;   (3) VAM inoculation   and  (4) Rhizobium-VAM inoculation. The second  factor  was the kind of varieties  namely  Edamame  and Wilis. There were 24 research  units  which  contain  12 polybags  of each unit. The result of  this  research   showed   that  there  was  no  interaction   between inoculation treatments and kinds of  varieties   to all  of  parameters, except the  percentage of mycorrhizae infection.  Inoculation  of Rhizobium  and VAM significantly  increased  the growth and yield of Wilis variety.  The  100 grains  weight  of Edamame   variety  was  23.21  g and  Wilis  variety  was 7.49  g. Inoculation  of Rhizobium  on Wilis variety was more compatible than Edamame.  Endogenus  VAM application on Edamame  variety was more compatible than VAM isolates inoculation.